Antibiosis in wheat interacts with crowding stress to affect Metopolophium dirhodum development and susceptibility to malathion. Issue 2 (14th October 2014) - Clayson, Paul J.; Michaud, J.P.; van Emden, Helmut F.
Abstract We used a laboratory study to compare the performance of rose‐grain aphid, Metopolophium dirhodum (Walker) (Hemiptera: Aphididae), on the wheat cultivars 'Huntsman' (susceptible) and 'Rapier' (partially resistant) in both low density (uncrowded) and high density (crowded) colonies and examined the consequences for aphid susceptibility to malathion. Adult apterae that developed on Rapier wheat had their mean relative growth rate (MRGR) reduced by 6 and 9% under uncrowded and crowded conditions, respectively, whereas the crowding treatment reduced MRGR by 3%, but only in Rapier aphids. Rapier resistance also reduced adult dry weight by 13 and 14% under crowded and uncrowded conditions, respectively, whereas crowding reduced it by 34 and 35% in Rapier and Huntsman aphids, respectively. Development on Rapier substantially reduced the topical LC50 of malathion by 37.8 and 34.8% under crowded and uncrowded conditions, suggesting that plant antibiosis increased malathion susceptibility. By comparison, crowding only reduced the LC50 by 29.5 and 26.0% on Huntsman and Rapier. The LD50 data showed that reductions on aphid body size on Rapier and through crowding did not fully explain the differences in LC50. This was particularly in the values for crowded aphids that were actually 80% higher than for uncrowded ones. This apparent tolerance of crowded aphids, however, may partly be due to loss of insecticide from small aphids at dosing. Evidence of synergy between plant resistance and insecticide susceptibility raises the possibility of using reduced concentrations of pesticides to control aphids on resistant crop cultivars, with diminished impacts on non‐target and beneficial species important in integrated pest management (IPM) programs.